Outsourcing justice and the emergence of consumer Ombudsman regulatory frame-work - Omoola, Sodiq Olalekan; Mohamed, Nurah Sabahiah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
This study aims to examine the phenomenon of outsourcing access to justice in the consumer goods and service industry. It is argued that one of the primary functions of any government is the provision of access to and delivery of justice. However, in the consumer goods sector, regulatory reforms have enabled the government to outsource this function to private ADR service providers or consumer ombudsman. The paper adopts doctrinal methodology through the analysis of consumer ombudsman regulations and annual reports of private ADR entities in the United Kingdom. The study finds that outsourcing justice to consumer ADR entities through appropriate legal framework is capable of ensuring the attainment of consumer protection objectives and enhances access to justice, without jeopardising the interest of businesses and consumers. Literature on outsourcing focuses on legal services outsourcing to private law firms to represent government interest. Outsourcing justice is unique as an emerging trend in consumer protection and dispute resolution with minimal government intervention. In an era of privatisation of government services and pursuit cost saving measures, alternative regulatory model is suitable through outsourcing consumer protection regulations to ADR entities.